DISCOURSE OF GRAMMATICAL AND LEXICAL COHESION IN THE NOVEL GALAKSI BY POPPI PERTIWI - Saputri, Risma (Kantor Bahasa Maluku Utara, 2024)
This article aims to: (1) find lexical and grammatical cohesion in Poppi Pertiwi's novel